Improving Sharia Economic Literacy from an Early Age Through Contextual Learning at Ma'had Darussalam Islamic Elementary School - Ahmad Syathiri; Rifani Akbar Sulbahri; Yulia Hamdaini Putri; Wita Farla WK (Ali Institute of Research and Publication, 2026)
Schools play a vital role in providing quality education and shaping students with strong character and morals. SD Islam Ma’had Darussalam functions not only as an educational institution but also as an agent of change committed to developing students with noble character, environmental awareness, and Islamic values from an early age. This community service activity aimed to socialize ethical and moral values aligned with Islamic economic principles in daily life. The activity was conducted through training and workshops for teachers, supported by learning modules as instructional materials. The results showed a significant improvement in teachers’ competence in teaching Islamic economic values. Evaluation results increased from 42% in the pre-test to 92% in the post-test, indicating a 50-percentage-point improvement after the intervention. These findings demonstrate that the training program effectively strengthened teachers’ pedagogical readiness and capacity to integrate Islamic economic values into classroom learning.